RhoC interacts with integrin α5β1 and enhances its trafficking in migrating pancreatic carcinoma cells. - Ningfeng Fiona Li (Public Library of Science (PLoS), 2013)
Human pancreatic ductal adenocarcinoma (PDAC) is characterized by early systemic dissemination. Although RhoC has been implicated in cancer cell migration, the relevant underlying molecular mechanisms remain unknown. RhoC has been implicated in the enhancement of cancer cell migration and invasion, with actions which are distinct from RhoA (84% homology), and are possibly attributed to the divergent C-terminus domain. Here, we confirm that RhoC significantly enhances the migratory and invasive properties of pancreatic carcinoma cells. In addition, we show that RhoC over-expression decreases cancer cell adhesion and, in turn, accelerates cellular body movement and focal adhesion turnover, especially, on fibronectin-coated surfaces. Whilst RhoC over-expression did not alter integrin expression patterns, we show that it enhanced integrin α5β1 internalization and re-cycling (trafficking), an effect that was dependent specifically on the C-terminus (180-193 amino acids) of RhoC protein. We also report that RhoC and integrin α5β1 co-localize within the peri-nuclear region of pancreatic tumor cells, and by masking the CAAX motif at the C-terminal of RhoC protein, we were able to abolish this interaction in vitro and in vivo. Co-localization of integrin α5β1 and RhoC was demonstrable in invading cancer cells in 3D-organotypic cultures, and further mimicked in vivo analyses of, spontaneous human, (two distinct sources: operated patients and rapid autopsy programme) and transgenic murine (LSL-KrasG12D/+;LSL-Trp53R172H/+;Pdx-1-Cre), pancreatic cancers. In both cases, co-localization of integrin α5β1 and RhoC correlated with poor differentiation status and metastatic potential. We propose that RhoC facilitates tumor cell invasion and promotes subsequent metastasis, in part, by enhancing integrin α5β1 trafficking. Thus, RhoC may serve as a biomarker and a therapeutic target.